Denpasar heritage track: Revitalisasi paket wisata ‘Denpasar city tour’ - I Nyoman Darma Putra; Syamsul Alam Paturusi; Widiastuti . (Universitas Udayana, 2017)
Bali’s capital city of Denpasar has a number of heritage sites, including several buildings, museums and monuments. These sites have yet to be developed optimally as tourist attractions, as evidenced by their small number of annual visitors. This study explores the potential in reutilizing those cultural heritage sites for the development of heritage tourism, and to support the city government’s tour programme. Two interrelated issues discussed here include how the government of Denpasar preserves its cultural heritage, and how it promotes these sites as heritage tourism. Data were collected through observation, interviews, and a literature review employing heritage tourism theory and framing theory. The study presents two packages of heritage tourism tours with a duration of approximately three hours each: the Denpasar Heritage Track (DHT), which starts and finishes at the Bali Hotel, taking in the Puputan Badung Monument, Bali Museum, Jero Kuta Palace, and Maospait Temple; and the Sanur Heritage Track (SHT), which begins and concludes at the Grand Bali Beach Hotel, visiting the Belanjong Heritage, Intaran Market, Bajra Sandhi Monument, and Museum Le Mayeur. The DHTs are expected to increase the number of tourist attractions in Denpasar, contributing to more tourist visits to Bali, especially in its capital city.